KAJIAN ETNOBOTANI DAN BIOAKTIFITAS TUMBUHAN OBAT KABUPATEN TAPANULI UTARA - Sinaga, Alex; Adelya I Manalu (Universitas Imelda Medan, 2021)
Traditional medicinal plants have the potential for health maintenance and alternative medicine as well as increasing the competitiveness of the national economy because Indonesia is one of the countries rich in biodiversity. This research was conducted in March-June 2021 in Tapanuli Regency, North Sumatra, 3 different villages that are part of the Parmonangan sub-district, namely, Aekraja Village, Hutatinggi Village, Sisordak Village. The objectives to be achieved are to find out how to use medicinal plants. The research method used includes selecting respondents for traditional healers, ethnobotanical surveys including field surveys, interviews and sampling of medicinal plants and preparing herbarium specimens. The results obtained were then analyzed descriptively by calculating the index values ??of U, RFC and RI. Where the largest UV results are UV analysis, the Zingiber officinale value is found to have a value (the largest UV is 0.4), and the highest RFC use values ??include: Zingiber Offiicinale (RFC 0.4), and the highest Relative Impotance values ??include: Zingiber Offiicinale (RFC 0.67) then Based on the results of bioactivity observations; It can be seen that the use of Zingiber officinale contains glucan chemical and polygalacturonan with biactivity as an antitussive. This traditional utility is attempted to be linked to reports from previous scientific studies published electronically such as PubMed, Google Scholar, PubChem, and ScienceDirect